Niche marketing: strategies for creating influence in the market - Ismail Razak (SEAN Institute, 2024)
In this era of globalization, competition in the market is increasingly fierce, and companies are looking for ways to differentiate themselves from competitors. Niche marketing has become an interesting approach, where companies focus on specific market segments with unique characteristics. This research aims to analyze and identify niche marketing strategies that are effective in creating influence in the market. This research uses a qualitative approach with descriptive methods. In the results of this research, it was found that implementing niche marketing strategies, including a deep understanding of consumer needs, unique products or services, appropriate pricing, and providing an extraordinary customer experience, significantly contributed to creating influence in the market. A company's reputation as an expert and leader in a limited niche market has also proven to be a major influence in strengthening its position and increasing consumer engagement. In conclusion, niche marketing can successfully create a lasting impact by combining product or service uniqueness, deep understanding of consumers, and meaningful personal interactions with customers in more focused market segments.